Education export as a form of knowledge transfer : The potential of Finnish education export in Chile - Räsänen, Elina (My University, 2012)
Knowledge transfer is a complex process. Knowledge transfer in the form of exporting education products from one system of education to another is particularly complicated, because each system has been developed in a particular context to meet the requirements seen as relevant at each time. National innovation systems are often seen to form an essential framework within which the development of a country, its economy and level of knowledge are considered and promoted. These systems are orientated towards the future, and as such they also provide a framework for the knowledge transfer related to the development of education. In the best of circumstances they are able to facilitate and boost this transfer both from the viewpoint of the provider and the recipient. The leading thought and the idea of the study is that education export is a form of knowledge transfer, which is illustrated by the existing models included. The purpose of this study is to explore, analyze and describe the factors and phenomena related to education export, and more specifically, those related to the experiences and potential of Finnish education export to Chile. For better understanding, of the multiplicity of the issue involved, the current status of education export between Finland and Chile and he existing efforts within the Finnish innovation network will be outlined as well as new forms of co-operation between Finland and Chile in educational matters explored. Several countries have started to commercialize their education system in order to establish themselves as emerging education exporters. Moreover, the demand for education reform is accurate in many developing countries. This offers a good match between Finland and Chile to be the example countries of the research. The main research findings suggest that there are several business areas in education export. These include degrees in education, training services and education technologies for example The factors that influence education export can be divided into four groups, including academic, cultural, political and economic aspects. Challenges to overcome include the lack of product or services to be sold, lack of market and cultural knowledge of the buyer country, financing and lack of suitable pricing model. National innovation systems could be seen as enabling entities for successful education export. The extensive networks that national innovation systems aim to form, could operate as a basis for joining the forces in selling knowledge as well as receiving knowledge in a constructive way.